2019
DOI: 10.1128/jvi.02147-18
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque Rhadinovirus Encodes a Viral Interferon Regulatory Factor To Disrupt Promyelocytic Leukemia Nuclear Bodies and Antagonize Type I Interferon Signaling

Abstract: Interferon (IFN) production and the subsequent induction of IFNstimulated genes (ISGs) are highly effective innate strategies utilized by cells to protect against invading pathogens, including viruses. Critical components involved in this innate process are promyelocytic leukemia nuclear bodies (PML-NBs), which are subnuclear structures required for the development of a robust IFN response. As such, PML-NBs serve as an important hurdle for viruses to overcome to successfully establish an infection. Both Kaposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The present knowledge also clearly suggested that vIRFs have ample impacts on both the KSHV and host gene expression, which conjointly contribute to KSHV life cycle as well as KSHV-associated pathogenesis. In fact, rhesus macaque rhadinovirus (RRV), which is closely related to the γ-herpesvirus KSHV and also encodes eight vIRFs, highlighted the importance of vIRFs in viral pathogenesis, as infection of vIRFs-knockout (KO) RRV in rhesus macaques showed reduced viral loads and significantly decreased B-cell hyperplasia [54,55]. Thus, future studies on the vIRFs will be necessary to confirm their roles during the viral life cycle and pathogenesis in a genetic context similar with RRV.…”
Section: Resultsmentioning
confidence: 99%
“…The present knowledge also clearly suggested that vIRFs have ample impacts on both the KSHV and host gene expression, which conjointly contribute to KSHV life cycle as well as KSHV-associated pathogenesis. In fact, rhesus macaque rhadinovirus (RRV), which is closely related to the γ-herpesvirus KSHV and also encodes eight vIRFs, highlighted the importance of vIRFs in viral pathogenesis, as infection of vIRFs-knockout (KO) RRV in rhesus macaques showed reduced viral loads and significantly decreased B-cell hyperplasia [54,55]. Thus, future studies on the vIRFs will be necessary to confirm their roles during the viral life cycle and pathogenesis in a genetic context similar with RRV.…”
Section: Resultsmentioning
confidence: 99%